Efektivitas Ruang Belajar Yang Inovatif Berbasis Teknologi Digital Dalam Pembelajaran PAI - Luthfi Febriani; Sania Tanzilaila; Ariel Sihabudin Aonillah; Afifah Fitria Hamdah; Fiqra Muhamad Nazib (Yayasan Al-Afif, 2025)
This study aims to analyze the literature review of the effectiveness of innovative learning spaces based on digital technology in Islamic Religious Education learning. This research method uses a Systematic Literature Review (SLR) which consists of the stages of determining the theme, searching, selecting literature, analyzing, compiling, and results. This study uses 11 articles from 25 articles obtained from various sources with publication years 2019-2024. This study focuses on 3 components: strategy, implementation and impact. The results of the study show that: 1) the strategies used in the application of digital technology in Islamic Religious Education learning vary widely according to the needs of students and the facilities available. 2) the implementation that can be carried out is also adjusted to the available media. 3) the resulting impacts have positive and negative sides, the positive impacts produced are in the form of increasing the quality of Islamic Religious Education education and student learning motivation, the negative impacts caused are dependence on technology and reduced conventional learning abilities.